The association of ApE1 -656T>G and 1349T>G polymorphisms with breast cancer susceptibility in northern Iran - Mashayekhi, F; Yousefi, M; Salehi, Z; Saedi, H S; Pournourali, M (Cellular and Molecular Biology, 2015)
Breast cancer is the most common cancer and one of the main causes of cancer-related death in the world and has become a major public health concern. Many genes have been shown to be involved in the progress of the breast cancer. Human apurinic/apyrimidinic endonuclease 1 (APE1) is a multifunctional protein that has an important role in the base excision repair (BER) pathway. The aim of this study was to evaluate the association between ApE1 -656T>G and 1349T>G polymorphisms and the susceptibility to breast cancer in northern Iran population. Samples were obtained from 150 patients diagnosed with breast cancer and 150 control subjects and genotyped by tetra - primer amplification refractory mutation system PCR (T-ARMS-PCR). We observed a significant difference in genotype distributions of -656T>G polymorphism between patients and controls (P= 0.03). Findings indicated that individuals with the variant TG genotypes had a significant decreased risk of breast cancer (OR= 0.55, 95% CI= 0.33 - 0.91, P= 0.019). However, the significant association between 1349T>G polymorphism and breast cancer risk was not observed (P = 0.89). Larger studies are needed to confirm our results.